Experiências: a mulher na liderança de Instituições de educação superior - Rocha, Cristina Fogaça (Universidade do Vale do Rio dos Sinos, 2018)
Female leadership in the labour market is gaining increasing awareness, but is still considered a challenge for research. Studies on the subject in recent years indicate how development is needed in Brazilian society, and that considerable in-depth research is still required in order to implement the social and institutional changes. In this context, the general objective of this research is to analyse the factors that influence the reduced number of women in roles of leadership in the higher education institutions of the metropolitan area of Porto Alegre - RS. The chapter ‘the beginning of the journey’ presents the theoretical framework that was developed with respect to the state of knowledge, the woman in Brazilian society, work in women's lives, management in higher education and women's leadership. The chapter ‘the road travelled’ presents the chosen methodology for the study which occurred through a qualitative research of exploratory nature. Data collection was conducted through literature review, as well as through interviews with three deans and one faculty director of the metropolitan region of Porto Alegre - RS. The chapter ‘conquering the top’ presents the analysis and discussion of the results, and the categories which emerged from the literature review and interviews, as follows; Gender: differences and prejudice; Family: absences and complicity; Management: achievements and challenges; and leadership and it’s teachings. Through the study, we were able to present a profile of the interviewed leaders, describing their training and career paths in their institutions as well as accounts of their experiences in the highest executive office. In addition, the results prompted a proposal for an extension course aimed at addressing women’s context in higher education, the ticket to career advancement, institutional space, experiences and management adversity. Finally, the conclusion presented the final considerations, while also highlighting the scarcity of similar studies on this subject in Brazil - a complex subject requiring deeper research. It can therefore be considered as a new form of research.
Keywords: Educação superior; Gestão; Liderança feminina; Higher education; Management; Women's leadership; ACCNPQ::Ciências Humanas::Educação